EVALUATION OF TARIFFS OF TRANSPORTING NATURAL GAS (TOLL FEES) ON PIPE SECTION X BY ANALYZING THE SENSITIVITY THE SENSITIVITY OF THE COST OF SERVICE PARAMETERS - Aulia Alfath; Bayu Satiyawira; Cahaya Rosyidan; Havidh Pramadika; Ratnayu Sitaresmi; Livia Ailen Dharma (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2020)
Indonesia has large enough gas reserves to meet household and industrial needs. It's just that, the price or the existing gas-related system is not maximal yet. One of the things that can ease the burden on the state is the use of household gas networks, some people are still hesitant to use it even though the price is relatively cheap compared to LPG. In determining the gas price, one of the components that has an effect on determining the gas price is the toll fee through pipes to be channeled. So the authors aim to conduct this research in order to educate and maximize solutions for energy dependency, for example the location I took is located in North Sumatra Province, with a pipeline stretching 156.5 km from X1 to X3. With OD 16